Prevalence of noncommunicable diseases and their risk factors among the population residing in the villages under a subcenter in Hassan: A community-based cross-sectional study - Prianka Shashi Kumar; G M Venkatesh; Anjan Sreeranga (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: In India's rural areas, there is an epidemiological shift toward the prevalence of noncommunicable diseases (NCDs). This study identified the prevalence and associations of risk variables for the development of NCD in Hassan, Karnataka. METHODOLOGY: From February 15, 2022, to April 30, 2022, a community-based cross-sectional survey was conducted among adults (18 years and older) residing in the 11 villages that make up the Hassan Medical College's rural field practice areas. A validated questionnaire was used to collect the data, and the SPSS trial version was used to analyze it. RESULTS: The total population was 765, of which 58.7% were female, 42% were illiterate, 91% were laborers, and 72.5% were from lower socioeconomic status. Among the participants, 59.6% were hypertensive, 7.4% were diabetic, 0.5% had cancer, and 0.3% had a cardiac disorder. Younger people (adjusted odds ratio [AOR] =2.406, confidence interval [CI] =1.747-3.315) and the unemployed (AOR = 2.131, CI = 1.355-3.353) had a higher risk of high blood pressure. Moreover, 9.4% of the participants used tobacco, which was significantly associated with the male gender (AOR = 2.161, CI: 1.289-3.622). About 5.5% consumed alcohol regularly, and being educated was found to be negatively associated with alcohol use (AOR = 0.126, CI = 0.044-0.363). CONCLUSION: Health education to modify lifestyle and improve adherence among patients consuming medicines should start at the individual level. Facilities need to be strengthened in the subcenters under all primary health center.